2015
DOI: 10.4103/0975-5950.168233
|View full text |Cite
|
Sign up to set email alerts
|

Technical complications of implant-causes and management: A comprehensive review

Abstract: Given the increasing popularity of dental implants, the number of failures due to late implant fracture is also expected to increase. Hence, the scope for prevention and management needs to be emphasized. The objective of this review article is to analyze the various causes of failure of dental implants due to implant fixture/abutment screw fractures and also to enumerate the management and the preventive options for these failures, thereby aiming to help the clinicians to properly plan the implant-supported p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 36 publications
1
53
0
1
Order By: Relevance
“…This indicates that peri-implant diseases may be related to the invasion and colonization of implants by these bacteria. 8 An unstable implant-abutment connection can also cause mechanical complications such as screw loosening, which is often seen in implant-supported single crowns. 7 Evidence has shown that fabrication tolerance, connection design, abutment material, and insertional torque can all affect the stability and integrity of the implant-abutment interface.…”
mentioning
confidence: 99%
“…This indicates that peri-implant diseases may be related to the invasion and colonization of implants by these bacteria. 8 An unstable implant-abutment connection can also cause mechanical complications such as screw loosening, which is often seen in implant-supported single crowns. 7 Evidence has shown that fabrication tolerance, connection design, abutment material, and insertional torque can all affect the stability and integrity of the implant-abutment interface.…”
mentioning
confidence: 99%
“…The implant‐abutment interface connection can be internal connection or external connection. The internal connection has a much more important role in the stability of abutments and force distribution compared with the external connection …”
Section: Discussionmentioning
confidence: 99%
“…Screw tightening produces tension in the screw, which causes elastic recovery and pulls the abutment and implant toward each other, creating a clamping force. Applying an adequate preload has some advantages such as lower micromotion of implant‐abutment screw interface, less frequency of screw loosening, improvement of fatigue resistance, and the locking of implant‐abutment connection …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The late implant failure has been reported after the prosthetic treatment and constitutes one of the major causes of implant loss after the osseointegration process (Derks et al 2015;Gupta et al 2015). It is mainly related to the implant-abutment misfit as a result of the abutment screws loosening.…”
mentioning
confidence: 98%